Selected women`s legal right in the family: a critical analysis of the Muslim feminist discourse - Haneef, Sayed Sikandar Shah (2014)
Muslim feminist, beyond the polemics of its ideological orientation, represents the voice of gender equality in the Muslim world. To them, traditional Islamic jurisprudence contains misogynic views regarding legal status of the female gender which by origin are the projection of patriarchal norms and cultural ethos of the pre-Islamic and medieval eras into textual evidences of Islamic law. They argue that such portrayal of women`s legal rights cannot be sustained in view of egalitarian principle of justice and equality as ordained by the Qur`an. Accordingly, to overcome the problem of disparity between men and women the whole classical Islamic law needs to be deconstructed and an alternative egalitarian narrative be produced. To respond to this challenge, the mainstream discourse is one of emotional outburst and condemnation rather than that of methodological engagement. In this contested intellectual battle, the real losers are the women in Muslim societies in general and in Southeast Asian countries, such as Malaysia in particular. To bridge the gap and ease tension, this paper, argues for mediating the issue within the frame of traditional Islamic methods of reform and renewal by using critical content analysis of both feminist and conservative methodologie.